Changing patterns of land access, inheritance and emerging female village headpersons in a patriarchal society among the Tumbuka in Northern Malawi - Alister C. Munthali; Erling Berge; Stanley Khaila; Daimon Kambewa; Henrik Wiig (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2024)
The Tumbuka are normally described as patrilineal where inheritance of property including land, cattle and village headmanship is from father to son. There is evidence that initially the Tumbuka were matrilineal. In this society, village heads are normally men, and land and other property are owned and inherited by men. However, there is an emergence of female village headpersons in this patrilineal society. This paper, using data from the Malawi Land Tenure and Social Capital (MLTSC) project, examines the factors that have led to this change and implications for residence at marriage. The study found that female village headpersons are largely single and that they are also chosen because there is no son or eligible male in the lineage to inherit the village headmanship. In terms of land inheritance, although land is largely inherited by sons, there is evidence from the data that in cases where there are no sons land can be inherited by daughters. Daughters also have access to land if they are divorced and they return to their natal villages. While inheritance rules exist, this paper shows that they are not as rigid.
hdl:11250/3131620
Keywords: Q15; P48; K15; K38; 330; Malawi; land tenure; village headperson; gender; Tumbuka